2017
DOI: 10.1007/s40333-017-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of salt expansion in sodium saline soils under transient conditions

Abstract: Salt expansion in sulfate saline soils that are widely distributed in northwestern China causes serious infrastructural damages under low-temperature conditions. However, the mechanism of salt expansion under low temperatures is not clear. In this study, we conducted a series of cooling experiments combined with salt crystallization to study this mechanism, and employed an ionic model to calculate the supersaturation ratio of the solution. During the experiments, the strength and the process of salt expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 14 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…In addition, standard sand with uniform gradation distribution is used to prepare dry sulfate saline soil samples for the tests in this paper, while salt expansion of sulfate saline soil is also significantly affected by the particle size distribution, density, porosity, and overlying load of the soil sample [5, 10-14, 20, 26]. e effects of these factors on salt expansion are more complicated [10,13,14], which need to be verified by further research.…”
Section: Discussion On the Salt Expansion Of Sulfate Saline Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, standard sand with uniform gradation distribution is used to prepare dry sulfate saline soil samples for the tests in this paper, while salt expansion of sulfate saline soil is also significantly affected by the particle size distribution, density, porosity, and overlying load of the soil sample [5, 10-14, 20, 26]. e effects of these factors on salt expansion are more complicated [10,13,14], which need to be verified by further research.…”
Section: Discussion On the Salt Expansion Of Sulfate Saline Soilmentioning
confidence: 99%
“…Wu et al [12] and Wan et al [13] investigated the salt expansion characteristics of sulfate saline soil under variable water content. Wan et al [14,15] studied the precipitation law of sodium sulfate decahydrate crystals in sulfate saline soil during the cooling process and established the relationship between varying water content and temperature reduction. Chen et al [16] and Lv et al [17] experimentally studied the reduction law of salt expansion of sulfate saline soil under the action of insulating layer and soilbag.…”
Section: Introductionmentioning
confidence: 99%
“…When the water content and the degree of compaction are under the same level, the salt expansion rate of the Qinghai silty clay shows an increasing tendency with the decrease of the cooling rate. Wan et al [8] found that the salt expansion rate of sulfate saline soil increased with a reduced cooling rate through the one-dimensional salt expansion test under closed conditions. As the cooling rate decreases, the water and salt migration behavior become more distinct.…”
Section: Effect Of Cooling Gradient On the Expansion Ratementioning
confidence: 99%
“…e salt crystallization behavior is driven by the temperature difference between daytime and nighttime, and such dissolution effect may easily cause engineering diseases in the continuous salt swelling-collapse process. To better illustrate the temperature effect on the salt expansion process, Lai et al [7] and Wan et al [8,9] conducted salt expansion experiments with different cooling rates. In conclusion, with an increased initial concentration of sulfate content, the cooling rate is slowed down, followed by decreased maximum supersaturation rate, increased salt crystallization rate, and higher salt expansion rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation